Evaluation of a Rhenium(I) Complex and Its Pyridostatin-Containing Chelator as Radiosensitizers for Chemoradiotherapy - António Paulo; Sofia Cardoso; Edgar Mendes; Elisa Palma; Paula Raposinho; Ana Belchior (Molecules)
The use of radiosensitizers is a beneficial approach in cancer radiotherapy treatment. However, the enhancement of radiation effects on cancer cells by radiosensitizers involves several different mechanisms, reflecting the chemical nature of the radiosensitizer. G-quadruplex (G4) DNA ligands have emerged in recent years as a potential new class of radiosensitizers binding to specific DNA sequences. Recently, we have shown that the Re(I) tricarbonyl complex PDF-Pz-Re and its pyrazolyl-diamine chelator PDF-Pz, carrying a N-methylated pyridostatin (PDF) derivative, act as G4 binders of various G4-forming DNA and RNA sequences. As described in this contribution, these features prompted us to evaluate PDF-Pz-Re and PDF-Pz as radiosensitizers of prostate cancer PC3 cells submitted to concomitant treatment with Co-60 radiation. The compound RHPS4 was also tested, as this G4 ligand was previously shown to exhibit strong radiosensitizing properties in other cancer cell lines. The assessment of the resulting radiobiological effects, namely through clonogenic cell survival, DNA damage, and ROS production assays, showed that PDF-Pz-Re and PDF-Pz were able to radiosensitize PC3 cells despite being less active than RHPS4. Our results corroborate that G4 DNA ligands are a class of compounds with potential interest as radiosensitizers, deserving further studies to optimize their radiosensitization activity and elucidate the mechanisms of action.